Green marketing and purchasing decisions among teenagers: an empirical perspectives - Sukri, Suriani; Meterang, Nurshila; Waemustafa, Waeibrorheem (INSInet Publications, 2015)
The objective of this paper is to identify relationship between green marketing and purchasing decision among teenagers. A convenience sampling method was employed from university students enrolled in Malaysia, who have embarked on green marketing successfully. Eight factors were found to be critical for purchasing decisions among teenagers. The factors are demographic, environmentally conscious consumer behaviour, perceived consumer effectiveness, environmental concern, liberalism, eco-brand and green marketing advertisement. The paper provides a framework for future research to explore the teenagers purchasing decisions.